A teatralização do “eu” das marcas: chatbots como ferramenta de humanização da marca sob o olhar de Erving Goffman - Kramer, Priscila Nogueira Kruger (2020)
Chatbot is an automated conversation software that aims to emulate human dialogical behavior. Currently, is gaining space in the advertising market as a tool that acts in the process of humanizing brands. Based on the Theory of Theatricalization of the Self, proposed by Erving Goffman, three chatbots served by brands on the Facebook Messenger platform were analyzed in order to understand how brands are building their selves using these automated chat software. In this way, first an exploratory research was carried out with the objective of identifying conversation robots used by brands within the Brazilian market, which were shown on Facebook Messenger during the first half of 2020 and with different marketing objectives. From this mapping, three bots methodologically different from each other were selected to be analyzed from the interactionist concepts proposed by Erving Goffman: Amora (Americanas.com); Beta (Nossas laboratory) and Fabi Grossi (UNICEF). It was concluded that, in the process of creating and programming these conversation robots, the approximation with stages correlated to the Theory of Theatricalization of the Self enhances their anthropomorphizing and their reflexes in the affective brand-public bond.